Arquitetura da rede e regulação: a neutralidade da rede no Brasil - Ramos, Pedro Henrique Soares (2015)
This thesis presents an analytical framework for the network neutrality regulation in Brazil, as set forth in ACT n. 12.965, which has been internationally recognized as the 'Marco Civil'. The research strategy involves mapping the main tensions and debates emerging from the subject in Brazil and an examination of the costs and benefits involved with the regulation of this principle. Chapter I presents a literature review, organizing the main positions in different categories according to a regulatory perspective. Chapter 2 presents a descriptive map of the institutional matrix of net neutrality in Brazil, encompassing the regulatory framework, the interest groups and how these elements made influence on the development of Marco Civil. Chapter 3 presents an exercise of interpretative framework for net neutrality regulation in Brazil, based on different methods of legal interpretation. Chapter 4 follows on with this exercise, examining the relationship between the net neutrality obligation set forth in Marco Civil and two specific cases, which are the emergence of complex business models on the network layer of the internet and zero-rating initiatives. Finally, Chapter 5 presents a perspective regulatory framework for regulators that will have to deal with the enforcement of Marco Civil.